PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD (STUDENT TEAMS ACHIEVEMENT DIVISIONS) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDN 012 BESILAM BARU DUMAI - Doharna '; Mahmud Alpusari Mahmud Alpusari; Munjiatun ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract, This research is motivated by the lack of science learning outcomes students class V of SDN 012 Besilam Baru Dumai. For that teachers use varied instructional models that can improve learning outcomes. Formulation of the problem in this study is whether the implementation of cooperative learning STAD (Student Teams Achievement Divisions) to improve science learning outcomes students class V of SDN 012  Besilam Baru Dumai?. This study aims to improve science learning outcomes class V students of SDN 012 New Besilam with material water cycle and natural resources. The design of this study is action research (CAR) conducted as many as two cycles, each cycle consisting of two meetings and one-time daily tests. From this study the activity of teachers' observations obtained in the first cycle the first meeting with the percentage of 66.7% is quite categories, the second meeting with a percentage of 87.5% is very good category. At the first meeting of the second cycle category percentage of 87.5% is very good and at the second meeting of the percentage to 96% category very well. While observations of student activity also increased, at the first meeting of the first cycle percentage 43.4% increase in the unfavorable category II meetings to 51.8% (not good). Cycle II was increased at the first meeting of the percentage increases of 69.6% and also at the meeting to the second 88% category very well. The results also showed an increase in student learning, in the first cycle an average of 70.8 student learning outcomes (Good) rose to 84.3 in siklsu II (Good). Likewise, the classical completeness students where both categories in percentage 84% increase in the category very well at 100% completion percentage. It can be concluded that the application of Cooperative Learning Model Type STAD (Student Teams Achievement Divisions) can improve learning outcomes IPA class V Students SDN 012  Besilam Baru Dumai. Keywords: STAD (Student Teams Achievement Divisions), Science Learning Outcomes